1985
DOI: 10.1203/00006450-198508000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Caries Resistance in Children with Chronic Renal Failure: Plaque pH, Salivary pH, and Salivary Composition

Abstract: ABSTRACT. W e studied properties of saliva and of dental plaque which affect the caries process in an effort to understand the low prevalence of caries in patients with chronic renal failure. Plaque pH, before and following carbohydrate exposure, saliva pEI, and saliva composition were evaluated in children and adolescents with chronic renal failure (n = 10) and successful renal transplantation (n = 1 I), and in two comparison groups of healthy children with few caries (n = 15) and numerous caries (n = 15).Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 4 publications
6
92
0
4
Order By: Relevance
“…Urea diffusing from saliva into dental plaque is converted to ammonia and carbon dioxide by bacterial ureases, while ADI catabolizes arginine to ornithine, ammonia, and CO 2 . An extreme example of the role of urea involves patients with chronic renal failure, who have salivary urea levels 5-to 25-fold higher than healthy controls and who have a very low caries incidence despite having to consume a diet composed primarily of carbohydrates (177). Furthermore, the levels of free arginine in the parotid saliva of caries-free adults were significantly higher than in adults with a history of dental decay (236).…”
Section: Production Of Alkalimentioning
confidence: 99%
See 1 more Smart Citation
“…Urea diffusing from saliva into dental plaque is converted to ammonia and carbon dioxide by bacterial ureases, while ADI catabolizes arginine to ornithine, ammonia, and CO 2 . An extreme example of the role of urea involves patients with chronic renal failure, who have salivary urea levels 5-to 25-fold higher than healthy controls and who have a very low caries incidence despite having to consume a diet composed primarily of carbohydrates (177). Furthermore, the levels of free arginine in the parotid saliva of caries-free adults were significantly higher than in adults with a history of dental decay (236).…”
Section: Production Of Alkalimentioning
confidence: 99%
“…Urease is a nickel-containing oligomeric enzyme that catalyzes the hydrolysis of urea to two molecules of ammonia and one molecule of carbon dioxide (161). Levels of 3 to 10 mM urea are found in the saliva of healthy individuals (100), although this can range up to 30 mM in patients with renal disease (177). Urease is produced by a discrete subset of oral bacteria, including S. salivarius, Actinomyces naeslundii, and oral haemophili.…”
Section: Production Of Alkalimentioning
confidence: 99%
“…In fact, relatively significant concentrations of urea are available to oral micro-organismsgenerally between 3 and 10 mM in saliva from healthy individuals (Golub et al, 1971;Kopstein and Wrong, 1977). In patients with renal disease, the concentrations of urea can range up to as much as 30 mM in saliva (Peterson et al, 1985) and 60 mM in gingival crevicular fluid (Golub et al, 1971). The results from early studies, which have been confirmed over a 20-year period, indicate that urea is rapidly metabolized in the mouth by resident bacteria expressing urease activities.…”
Section: (B) Role Of Salivary Urea In Protecting the Oral Streptococcmentioning
confidence: 99%
“…KEYWORDS bacteriocin, biofilm, dental caries, genetic competence, transcription profiling S treptococci are the primary colonizers of the human oral cavity and are among the most abundant genera constituting the biofilms on the soft and hard tissues of the mouth (1, 2). Oral biofilms are highly organized communities of a physiologically and genetically diverse group of microorganisms, many of which are commensal or overtly study showed that subjects with chronic renal failure, who can secrete an amount of urea in saliva that is 10-fold or more higher than that of healthy subjects, seldom developed dental caries despite consuming a diet composed predominantly of carbohydrates (18,19). Furthermore, when rats were infected with S. mutans or a recombinant derivative of S. mutans that expressed the urease genes of Streptococcus salivarius, the rats infected with the strain expressing high levels of urease developed fewer and less-severe carious lesions than those infected with the parental strain when fed a cariogenic diet supplemented with urea (20).…”
mentioning
confidence: 99%